On a small collection of Maeridae Krapp-Schickel, 2008 (Crustacea: Amphipoda) from Gujarat, India - Thacker, Dimple; Myers, Alan A.; Trivedi, Jigneshkumar N. (Zootaxa, 2024)
The present study was based on amphipod specimens collected from the coastal areas of Gujarat state, India. From the collection, four species belonging to the family Maeridae Krapp-Schickel, 2008 were identified. Two species, Ceradomaera plumosa Ledoyer, 1973 and Ceradocus (Denticeradocus) alama Myers & Nithyanandan, 2016 are reported for the first time from Gujarat state and India, respectively. Two more species, Maera gujaratensis sp. nov. and Quadrimaera okha sp. nov. are described as new species. Maera gujaratensis sp. nov. can be differentiated from its closely related congener M. hirondellei Chevreux, 1900 on the basis of shape of male gnathopod 1 coxa and number of setae present on the telson. Quadrimaera okha sp. nov. can be differentiated from its closely related congeners Q. brownorum Hughes, 2015 and Q. caliban (Ruffo, Krapp & Gable, 2000) by the non-lobate anterodistal corner of gnathopod 2 basis, by the shape of the propodus of the male gnathopod 2, and in having a comparatively smaller uropod 3 peduncle to rami ratio.